Endotoxin Mass Concentration in Plasma Is Associated With Mortality in a Multicentric Cohort of Peritonitis-Induced Shock - Payen, Didier; Dupuis, Claire; Deckert, Valérie; Pais de Barros, Jean-Paul; Rérole, Anne-Laure; Lukaszewicz, Anne-Claire; Coudroy, Remi; Robert, René; Lagrost, Laurent (Frontiers in Medicine, 2021)
Objectives: To investigate the association of plasma LPS mass with mortality and inflammation in patients with peritonitis-induced septic shock (SS). Design: longitudinal endotoxin and inflammatory parameters in a multicentric cohort of SS. Patients: protocolized post-operative parameters of 187 SS patients collected at T1 (12 h max post-surgery) and T4 (24 h after T1)). Intervention: Post-hoc analysis of ABDOMIX trial Measurements and results: Plasma concentration of LPS mass as determined by HPLC-MS/MS analysis of 3-hydroxymyristate, activity of phospholipid transfer protein (PLTP), lipids, lipoproteins, IL-6 and IL-10. Cohort was divided in low (LLPS) and high (HLPS) LPS levels. The predictive value for mortality was tested by multivariate analysis. HLPS and LLPS had similar SAPSII (58 [48.5; 67]) and SOFA (8 [6.5; 9]), but higher death and LPS to PLTP ratio (p<0.01). LPS was stable in HLPS, but it increased in LLPS with a greater decrease in IL-6 (p<0.01). Dead patients had a higher T1 LPS (p=0.02), IL-6 (<0.01), IL-10 (=0.01) and day 3 SOFA score (p=0.01) than survivors. In the group of SAPSII > median, the risk of death in HLPS (38%) was higher than in LLPS (24%; p<0.01). The 28-day death was associated only with SAPSII (OR 1.06 [1.02;1.09]) and HLPS (OR 2.47 [1; 6.11]) in the multivariate model. In HLPS group, high PLTP was associated with lower plasma levels of IL-6 (p = 0.02) and IL-10 (p =0.05). Conclusions: Combination of high LPS mass concentration and high SAPS II is associated with elevated mortality in peritonitis-induced SS patients.